Calcineurin inhibitor‐sparing regimens based on mycophenolic acid after kidney transplantation. (29th January 2015) - Kamar, Nassim; Del Bello, Arnaud; Belliere, Julie; Rostaing, Lionel
Summary The use of calcineurin inhibitors (CNIs) has dramatically reduced the number of acute rejections and improved kidney allograft survival. However, CNIs can also cause kidney damage and several adverse events. This has prompted transplant physicians to use CNI‐sparing regimens. CNI withdrawal, minimization, or avoidance protocols have been conducted using mycophenolic acid (MPA), and/or mammalian‐target‐of‐rapamycin inhibitors, and/or belatacept. Herein, we review the outcomes of minimizing, withdrawing, or avoiding CNIs when giving mycophenolic acid to de novo and maintenance kidney transplant patients. Protocols on CNI withdrawal, when based on MPA without mammalian‐target‐of‐rapamycin inhibitors (mTORi) or belatacept, in de novo and maintenance kidney transplant patients, are associated with an increased risk of acute rejection. Consequently, these strategies have been abandoned and are not recommended. Protocols on CNI minimization show a beneficial impact of kidney function and acceptable acute rejection rates mainly in patients who have been recipients of a graft for >3–5 years. However, no significant improvement to graft survival has been observed.